The Impact of Global Alignment and Proportion Score and Bracing on Proximal Junctional Kyphosis in Adult Spinal Deformity. Issue 3 (April 2023) - Lord, Elizabeth L.; Ayres, Ethan; Woo, Dainn; Vasquez-Montes, Dennis; Parekh, Yesha; Jain, Deeptee; Buckland, Aaron; Protopsaltis, Themistocles
Study Design: Retrospective chart review. Objective: The goal of this study is to examine the relationship between global alignment and proportion (GAP) score and postoperative orthoses with likelihood of developing proximal junctional kyphosis (PJK). Methods: Patients who underwent thoracic or lumbar fusions of ≥4 levels for adult spinal deformity (ASD) with 1-year post-operative alignment x-rays were included. Chart review was conducted to determine spinopelvic alignment parameters, PJK, and reoperation. Results: A total of 81 patients were included; baseline and 1-year postoperative alignment did not differ between patients with and without PJK. There was no PJK in 53.1%, 29.6% had PJK from 10-20°, and 17.3% had severe PJK over 20° (sPJK). At baseline, 80% of patients had severely disproportioned GAP, 13.75% moderate, 6.25% proportioned. GAP improved across the population, but improved GAP was not associated with sPJK. Greater correction of the upper instrumented vertebra to pelvic angle (UIV-PA) was associated with a larger PJK angle (PJKA) change (R = -0.28) as was the 1 year T1-upper instrumented vertebra (T1-UIV) angle (R = 0.30), both P < .05. GAP change was not correlated with PJKA change. Postoperative orthoses were used in 46% of patients and did not impact sPJK. Conclusions: There was no correlation between PJK and GAP or change in GAP. Greater correction of UIV-PA and larger postop T1-UIV was associated with greater PJKA change; suggesting that the greater alignment correction led to greater likelihood of failure. Postoperative orthoses had no impact on PJK.